LUSTRE: An Online Data Management and Student Project Resource. Issue 3 (18th November 2022) - Towse, John; Davies, Rob; Ball, Ellie; James, Rebecca; Gooding, Ben; Ivory, Matthew
Abstract: We advocate for greater emphasis in training students about data management, within the context of supporting experience in reproducible workflows. We introduce the L ancaster U niversity ST atistics RE sources (LUSTRE) package, used to manage student research project data in psychology and build capacity with respect to data acumen. LUSTRE provides a safe space to engage students with open research practices—by making tangible different phases of the reproducible research pipeline, while emphasizing its value as a transferable skill. It is an open-source online data catalogue that captures key data management information about a student research project of potential relevance to data scientists. Embedded within a taught programme, it also highlights concepts and examples of data management processes. We document a portfolio of open teaching resources for LUSTRE, and consider how others can implement or adapt them to facilitate data management and open research. We discuss the role of LUSTRE as a; (a) resource and set of activities for promoting good data management practices; (b) framework to enable the delivery of key concepts in open research; (c) an online system to organize and showcase project work.